Pengembangan Media Video Tutorial untuk Materi Jurnal Visual di Kelas X SMA Negeri 5 Bukittinggi - Helsa Marsella Putri; Siti Aisyah (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
This research is a study of development of media video tutorials for learning visual arts in particular visual journal material in students of X grade State High School 5 Bukittinggi. The problem found is that learning is not optimal due to lack of use of learning media. Video tutorials can be used to support the learning process and help teachers deliver learning materials. This research uses the Research and Development method with a 4D model that consists of define, design, develop, and disseminate. Data analysis techniques use qualitative and quantitative descriptive analysis. The test subjects in this study were 42 respondents consisting of 5 experts, 1 cultural art teacher, and 37 students. The results of the study showed that the media, material, and language validation test reached a score of 80-90%. Next, the practicality test by the teacher obtained a rating of 86.67%, the student response rating of the small-scale test obtaining a 94.9% score and the large scale trial obtains a grade of 91.81%. The final stage is the test of effectiveness gained from the pre-test and post-test results. Small scales obtain t_count of 7.17 bigger than t_table of 1.894. Large scales get t_counters of 7.68 larger than tables of 1.701. It can be concluded that the video tutorial media product developed on learning visual arts in particular visual journal material has proven valid, practical and effective to use.